Drag analysis of an aircraft wing model and without bird feather like winglet - Hossain, Altab; Rahman, Mohammed Ataur; Iqbal, A.K.M. Parvez; Ariffin, Muhidin; M., Mazian (World Academy of Science, Engineering and Technology, 2012)
This work describes the aerodynamic characteristic for aircraft wing model with and without bird feather like winglet. The aerofoil used to construct the whole structure is NACA 653-218 Rectangular wing and this aerofoil has been used to compare the result with previous research using winglet. The model of the rectangular wing with bird feather like winglet has been fabricated using polystyrene before design using CATIA P3 V5R13 software and finally fabricated in wood. The experimental analysis for the aerodynamic characteristic for rectangular wing without winglet,wing with horizontal winglet and wing with 60 degree inclination winglet for Reynolds number 1.66×105, 2.08×105 and 2.50×105 have been carried out in open loop low speed wind tunnel at the Aerodynamics laboratory in Universiti Putra Malaysia. The experimental result shows 25-30 % reduction in drag coefficient and 10-20 % increase in lift coefficient by using bird feather like winglet for angle of attack of 8 degree.